The Bivalent Side of the Nucleus Accumbens - Levita, Liat (2008)
An increasing body of evidence suggests that the nucleus accumbens (NAcc) is engaged in both incentive reward processes and in adaptive responses to conditioned and unconditioned aversive stimuli. Yet, it has been argued that NAcc activation to aversive stimuli may be a consequence of the rewarding effects of their termination, i.e., relief. To address this question we used fMRI to delineate brain response to the onset and offset of unpleasant and pleasant auditory stimuli in the absence of learning or motor response. Increased NAcc activity was seen for the onset of both pleasant and unpleasant stimuli. Our results support the expanded bivalent view of NAcc function and call for expansion of current models of NAcc function that are solely focused on reward.